2005
DOI: 10.1016/j.bbadis.2004.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine protects against the inactivation of esterase induced by glycation and a steroid

Abstract: Carnosine, an endogenous histidine-containing dipeptide, protects protein from oxidation and glycation, which may contribute to a potential treatment for some conformational diseases including cataract. Glycation, the non-enzymic reaction of sugars with proteins, promotes cross-linking and further aggregation. Prolonged use of glucocorticoids is a risk factor for cataract, as is diabetes. Esterase activity in the lens is decreased in senile cataract and diabetes. Previously, we reported that glycation and a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…The protective effect of MDA was explained by ability of carnosine to interact with aldehydes and ketones 11. This suggestion was confirmed very recently by other investigators 28…”
Section: Carnosine As a Natural Anti‐glycating Agentsupporting
confidence: 55%
“…The protective effect of MDA was explained by ability of carnosine to interact with aldehydes and ketones 11. This suggestion was confirmed very recently by other investigators 28…”
Section: Carnosine As a Natural Anti‐glycating Agentsupporting
confidence: 55%
“…Interestingly, it has been found that carboxylesterase activity in the lens decreases steadily with age due to glycation of the enzyme, 44 indicating a possible role in human cataract.…”
Section: Discussionmentioning
confidence: 99%
“…biochemical properties of carnosine, i.e. antioxidant effects and inhibition of AGE formation [22,24,[39][40][41][42], we expected that carnosine feeding would counteract these factors in kidneys of diabetic rats. Yet surprisingly, our results clearly show that carnosine feeding of diabetic rats is neither capable of preventing oxidative stress and AGE formation, nor could carnosine prevent the activation of the hexosamine pathway in our experimental setting, despite of carnosine feeding significantly increased renal carnosine concentrations.…”
Section: Discussionmentioning
confidence: 99%